2019
DOI: 10.5114/pg.2019.90253
|View full text |Cite
|
Sign up to set email alerts
|

The application of 24-hour pharyngeal pH-monitoring and Reflux Finding Score and Reflux Symptom Index questionnaires in the diagnostics of laryngopharyngeal reflux

Abstract: Introduction: Twenty-four-hour oesophageal pH-monitoring is a gold standard in the diagnostics of gastroesophageal reflux (GERD); however, this examination does not always perform well in patients in whom laryngeal symptoms of reflux are observed. Aim: To test the effectiveness of Reflux Symptom Index (RSI) and Reflux Finding Score (RFS) in confirming the occurrence of laryngopharyngeal reflux (LPR). Material and methods: Eighty-two patients with symptoms suggesting the occurrence of LPR were studied. The mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
1
5
0
1
Order By: Relevance
“…Other gastroenterologists agree with our opinion on these matters (23,24). Some researchers believe that age can affect the RSI diagnostic threshold for LPR (25), and another study using the Dx-pH system found that Ryan's scores, RSI, and RFS were poorly correlated with LPR detection (26).…”
Section: Discussionsupporting
confidence: 83%
“…Other gastroenterologists agree with our opinion on these matters (23,24). Some researchers believe that age can affect the RSI diagnostic threshold for LPR (25), and another study using the Dx-pH system found that Ryan's scores, RSI, and RFS were poorly correlated with LPR detection (26).…”
Section: Discussionsupporting
confidence: 83%
“…This suggests that most patients reported moderate to severe reflux symptoms at the time of their initial evaluation (Table II). However, the RSI is known to be relatively non‐specific 18 . Given the proportion of patients with known pathologic esophageal history at the time of evaluation, it is expected that the RSI will be elevated in this population.…”
Section: Resultsmentioning
confidence: 99%
“…W diagnostyce dolegliwości ze strony gardła i krtani 24-godzinna pH-metria gardłowa wydaje się użytecznym narzędziem diagnostycznym w sytuacji, kiedy zarówno dolegliwości pacjenta (np. na podstawie RSI), jak i obraz endoskopowy krtani (RFS) sugerują występowanie refluksu krtaniowo--gardłowego [15].…”
Section: Dyskusjaunclassified